Is there post-meiotic transcriptional activity during hemipteran spermiogenesis? - Chaboli Alevi, Kaio Cesar [UNESP]; Mendonaca, Priscila Pasqueetto [UNESP]; Pereira, Nathalia Paiva [UNESP]; Rosa, João Aristeu da [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Taylor & Francis Ltd, 2014)
Different techniques have been used to evaluate post-meiotic nucleolar activity during spermatogenesis. However, the results have not been consistent, and transcriptional activity during spermiogenesis is still a highly debated issue. Through the use of cytogenetic tools, we evaluated whether the nucleolus is active during spermiogenesis in triatomines, more specifically, in Triatoma lenti. During spermatid differentiation, the nucleolus was observed using the cytogenetic technique of silver staining. Through the Feulgen reaction, we found that the silver ions had labeled the ribosomal DNA (rDNA). Using molecular cytogenetic techniques (DAPI and FISH), we were able to highlight the nucleolus and the Nucleolus Organizing Region (NOR) in spermatid images. Using the C-banding technique, we found rDNA and the NOR to be completely heterochromatic. Since this nuclear structure is present throughout the spermatid stage, we believe that the rDNA and NOR are inactivated by epigenetic factors, because we found a direct relationship between the nucleolus, rDNA, the NOR, and heterochromatin. Because heterochromatization of DNA is an important way to inactivate genetic material, we believe that the entire transcriptional activity required for cellular differentiation during spermiogenesis is mediated by the chromatoid body.
Keywords: cytogenetics; nucleolus; epigenetics; chromatoid body